Green bonds and other financial markets; diversification and volatility transmission patterns amidst COVID-19 - Saeed, Muhammad (2022)
The shift to a low-carbon economy and growing concern about the harmful impacts of climate change have heightened regulators' and investors' interest in environmentfriendly financial products. As a result, green bonds have emerged as one of the most promising possibilities for assisting in the mobilisation of financial resources for clean and sustainable initiatives. Despite the tremendous demand for green bonds, very few studies analyse how the green bonds market offers portfolio opportunities to investors. Hence, the prime objective of the study is to examine the coherence between green bonds and other financial markets (stock, commodity, digital currency, bonds, and foreign exchange markets) in constructing an efficient portfolio. This study used global data ranging from November 2008 to March 2021. To achieve the objective of the study, various methods such as quantile on quantile regression (QQR), wavelets analysis, Diebold and Yilmaz (2014) spillover index, and dynamic conditional correlations (DCC) were applied. The QQR analysis confirmed asymmetric dependency between green bonds and other financial markets subject to changes in market conditions (normal, bearish, or bullish). However, during COVID-19, the green bonds market negatively correlate with other financial markets across the quantiles. Meanwhile, the findings from wavelet correlation and continuous wavelet transformation confirmed that coherence between green bonds and other financial markets is more evident up to the middle of the time frame of the study. In addition, the Diebold and Yilmaz (2014) spillover index findings showed that during the COVID-19 pandemic, green bonds transmit volatility spillovers to other pairs of markets. Finally, DCC findings confirmed that the green bonds market act as a safe haven against other financial markets during financial turbulence periods. Furthermore, this study has practical policy implications for individual investors, fund managers and policy makers.